The Role of Linguistic Alignment on Question Development in Face‐to‐Face and Synchronous Computer‐Mediated Communication Contexts: A Conceptual Replication Study. Issue 3 (10th May 2020) - Kim, YouJin; Skalicky, Stephen; Jung, YeonJoo
Abstract: To date, linguistic alignment studies in second language acquisition have mainly been conducted during face‐to‐face (FTF) interactions. In the current study, we examined and compared the effect of structural alignment on the development of English direct and indirect questions in FTF and synchronous computer‐mediated communication (SCMC) contexts. Additionally, we assessed participants' working memory capacity and previous knowledge of the target structures. We assigned 50 Korean learners of English to either an FTF or SCMC modality. Over 3 weeks, they completed a pretest, two interactive alignment sessions, a working memory test, and immediate and delayed posttests. Results indicate that primed production of direct and indirect questions is significantly more likely than unprimed production. Moreover, we found an interaction with modality for primed production of direct questions but not for indirect questions. Findings suggest learning effects for direct questions only and that this effect is facilitated by the degree of alignment. Abstract :